Tribology of polymeric nanocomposites : friction and wear of bulk materials and coatings - Friedrich, Klaus, 1945- (Tribology and interface engineering series ;, 2008)
The area of tribology deals with the design, friction, wear and lubrication of interacting surfaces in relative motion. Polymer nanocomposite materials are increasingly common and offer remarkable improvements in the friction and wear properties of both bulk materials and coatings. This book gives a comprehensive description of polymeric nanocomposites, both as bulk materials and as thin surface coatings, and their behavior and potential use in tribological applications. It provides the preparation techniques, friction and wear mechanisms, properties of polymeric nanocomposites, characterization, evaluation and selection methodology. It also provides various examples of application of polymeric nanocomposites. * Provides a complete reference from the preparation to the selection of polymeric nanocomposites * Explains the theory through examples of real world applications * More than 20 international tribology experts contribute to their area of expertise.